Knowledge Management and Acquisition for Smart Systems and Services 13th Pacific Rim Knowledge Acquisition Workshop, PKAW 2014, Gold Cost, Qld, Australia, December 1-2, 2014. Proceedings - Kim, Yang Sok.; Kang, Byeong Ho.; Richards, Deborah; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the proceedings of the 13th International Workshop on Knowledge Management and Acquisition for Intelligent Systems, PKAW 2014, held in Gold Cost, Qld, Australia, in December 2014. The 18 full papers and 4 short papers included in this volume were carefully reviewed and selected from 69 initial submissions. They deal with knowledge acquisition, expert systems, intelligent agents, ontology engineering, foundations of artificial intelligence, machine learning, data mining, Web mining, information systems, Web and other applications.
Machine Learning and Data Mining -- Incremental Knowledge Acquisition -- Web-Based Techniques and Applications -- Domain Specific Knowledge Acquisition Methods and Application.
Keywords: Computer science; Computer Science; Computer Science, general; Electronic books